IMPLEMENTASI SELF LOVE PADA REMAJA - Devina Widi Astuti; Faqih Purnomosidi (Gapenas Publisher, 2023)
Adolescence is a time when it requires a lot of knowledge, in order to overcome the turbulent problems in that phase. Given that the adolescent phase is a transitional phase from children to adults who experience many changes from physical, psychological and psychosocial aspects. It is from this phase that many gourds are created, anxieties arise, and problems arise. One of the things that makes them teenagers less capable or confused in overcoming the problem is lack of self-love or planting love in themselves. Self love is a form of action that aims to love themselves, respect themselves, love themselves and respect themselves, so that if the application of self love is able to be created, it will be able to have a positive impact on their mental health. The method in this devotion is lectures and discussions. The informant or subject in this service is a teenager who is a grade XI MIPA 4 student at SMA Negeri 1 Polokarto and a teenage study congregation at the Nurul Huda Karangasem mosque Surakarta. The result of this dedication is to provide socialization related to the importance of implementing or implementing self-love in everyday life which aims to overcome anxiety. The conclusion from the results of this service is that informants or subjects are basically still minimal and lacking in the application of daily self-love because feelings of anxiety and stress and confusion dominate. The resource person provides ways or methods in the application of self-love such as being grateful, thinking positively, appreciating the achievements that have been passed